HUBUNGAN HARGA DIRI DENGAN KEBIASAAN MEROKOK PADA REMAJA DI DESA MENURAN KECAMATAN BAKI SUKOHARJO - Dinar Ariasti; Iva Puspita Sari (KOSALA : Jurnal Ilmu Kesehatan, 2018)
Background: Factors that can affect smoking habits in teenagers include the need forself-actualization, pressure or ridicule by peers if not smoking. Pressure in the form ofridicule makes an appreciation of a teenager's self decline and this condition is likely toaffect teens to start trying to smoke. When interviewed by several teenagers in the villageMenuran Baki Sukoharjo they smoke because follow-friends smoke and feel moreacceptable in the association when smoking.The purpose of this study was to determine the relationship of self esteem concept andsmoking habit in teenagers in Menuran Village Baki, Sukoharjo.The subjects The population in this study were male teenagers who smoked in the villageMenuran Baki Sukoharjo, based on preliminary surveyMethods: This research use correlation research design with cross sectional methodapproach. The data collection tool used is a questionnaire to measure the concept of selfesteemand Smoking Behavior by finding the primary data from Menuran village.The results of the study: There were 66.67% of respondents have positive self-esteemconcept and 33.33% of respondents have negative self-concept concept. There are71.43% of respondents have mild smoking habit and 4.76% respondents have smokinghabit in level weight. Result of test with Pearson Chi-Square Î± = 5% (0.05) got resultthere is relation of self-esteem concept with smoking habit at teenagers in Village ofMenuran District of Baki Sukoharjo with p = 0.001 so that p value <0.05.The conclusion of this study: There is a relationship of self esteem concept with smokinghabit in teenagers of Menuran Village Baki Sukoharjo.Keywords: Self-esteem Concept, Smoking Habit